Construction method of aerogel solid drug delivery system for treating blepharitis ciliaris

The antibacterial aerogel solid-state drug delivery system prepared by using organometallic frames and aerogel materials in the treatment of blepharitis has been solved, and the high cost and poor effect of blepharitis treatment has been achieved, achieving significant antibacterial and recurrence reduction effects have been achieved. .

CN119215008AActive Publication Date: 2024-12-31HEILONGJIANG UNIV OF CHINESE MEDICINE +1
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411185134.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-27
Publication Date
2024-12-31
Estimated Expiration
2044-08-27

AI Technical Summary

Technical Problem

The treatment of blepharitis has problems of high cost and poor treatment effect, and the disease is prone to recurrence, so the prior art is difficult to effectively improve the impact of immune factors on the disease.

Method used

An antibacterial aerogel solid-state drug delivery system is prepared by cross-linking reaction using an organic metal frame as a carrier, combining aerogel material and Ruyi Golden Powder volatile oil, and a solid-state drug delivery system is prepared by cross-linking reaction, and metal ions are gradually released to enhance the bactericidal effect.

Benefits of technology

It significantly improves antibacterial activity and therapeutic effect, and has better bactericidal effect than traditional dressings, reducing bacterial infection and inflammation, shortening the treatment cycle and reducing the risk of disease recurrence.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119215008A_ABST
    Figure CN119215008A_ABST
Patent Text Reader

Abstract

A construction method of an aerogel solid drug delivery system for treating blepharitis ciliaris belongs to the technical field of ophthalmology medical treatment, and adopts the scheme as follows: step 1, dissolving a partial polar drug in an ethanol solution to obtain a solution A, adding a metal frame carrier into the solution A, stirring, centrifuging and drying to obtain a partial polar drug-metal frame drug delivery system; step 2, fully crosslinking an aerogel material, a partial polar drug-metal framework drug delivery system and a crosslinking agent, adding a volatile oil component, and stirring until no bubble exists, so as to obtain a mixed glue solution B; or fully cross-linking the aerogel material, the volatile oil component and the cross-linking agent, stirring until no bubble exists, breaking into a thick liquid state, adding the partial polarity drug-metal framework drug delivery system, and uniformly stirring to obtain a mixed glue solution C; and step 3, freeze-drying the mixed glue solution B or the mixed glue solution B to obtain the aerogel solid-state drug delivery system for treating blepharitis ciliaris. The bactericidal effect of the dressing is obviously higher than that of traditional dressings.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of ophthalmic medical treatment, and in particular relates to a method for constructing an aerogel solid drug delivery system for treating blepharitis. Background Art

[0002] Blepharitis is a subacute and chronic inflammation of the eyelid skin, eyelash follicles and their glands. The eyelid area is rich in glandular tissue and fatty secretions, which are easily contaminated with dirt and bacteria and cause infection. Clinically, it is divided into three types: scaly, ulcerative, and canthal blepharitis. Scaly is eyelid eczematous dermatitis, which is caused by secondary infection due to excessive glandular secretion, and ulcerative is caused by staphylococcal infection of eyelash follicles and eyelid skin. Blepharitis is a chronic ocular surface disease that is difficult to cure and prone to recurrence. Its diagnosis and treatment are combined with antibiotics, Chinese medicine fumigation, external application, oral administration and ultrasonic atomization to improve the symptoms and signs of patients with blepharitis, but it still faces many problems and challenges. The long-term treatment cost of eye cleansers is high, and some patients still have poor results or recurrence. Immune factors may play an important role in the occurrence and recurrence of the disease. Therefore, it has become an urgent problem to give full play to the holistic concept of traditional Chinese medicine and its advantages of simplicity, convenience and low cost, treat according to syndrome differentiation, improve the body's immune environment to shorten the treatment cycle and reduce disease recurrence. Ruyi Jinhuang San (RHS) was first recorded in the Ming Dynasty's "Surgery Authenticity" as "all kinds of stubborn swelling and poison in surgery, use it at will, and it will be effective." It is included in the 2nd to 11th editions of the "Chinese Pharmacopoeia". It has the effects of clearing away heat and detoxifying, reducing swelling and relieving pain. It is mainly used for sores, swelling and pain caused by heat and toxic stagnation in the skin, and erysipelas. The symptoms are redness, swelling, heat and pain in the skin. It can also be used for traumatic injuries. Modern research shows that RHS can significantly improve wound healing. RHS is an immunomodulator [1] Its active ingredients can inhibit the expression of pro-inflammatory factors iNOS and COX-2 in macrophages, and can also inhibit the production of cytokines in plasma, so it has the effect of relieving physical pain.

[0003] An ideal wound dressing should have a variety of functional properties, including suitable surface structure, sufficient mechanical strength, high gas permeability, excellent biocompatibility, and effective antibacterial properties. Aerogels have a high specific surface area and are easy to quickly absorb exudate; high porosity ensures gas exchange between the wound and the outside world; and a unique three-dimensional network structure facilitates cell adhesion and proliferation, vascularization, and tissue reconstruction, so they have unique advantages in the field of wound repair. More and more aerogels with different compositions and structures are being used to repair different types of wounds. López-Iglesias C [2] et al. prepared chitosan aerogel loaded with vancomycin, and the release curve showed that the drug could be released quickly and could effectively reach the local treatment level. Antibacterial tests showed that it had good cell compatibility and could effectively prevent high bacterial load in the wound site. [3]et al. prepared a flexible antibacterial aerogel based on nanocellulose, in which the loaded cinnamaldehyde, microfibrillated cellulose and nanocrystals interacted with each other to form an antibacterial surface with a dense and uniform microstructure, which had long-term excellent antibacterial activity.

[0004] Organic metal frameworks (MOFs) are mainly metal-organic supramolecular network structures formed by the coordination of multidentate ligands and metal centers. Compared with other porous carrier materials, they have the following advantages: highly ordered pore structure, controllable pore size, and controllable functional groups and surface potential energy on the pore surface. Dong K et al. [4] loaded camptothecin into RGD-modified ZIF-8 organic metal frameworks, which showed good targeting and therapeutic effects and are expected to become potential drugs for tumor targeted therapy.

[0005] References:

[0006] [1]YuKwongleung,ChouYichun,Liu Chingshen,ChenYijia,YenMinghong.InducibleExpressionofNOS andCOX-2inEvaluating the Effects ofRuyi-JinhuangGao on S-omaticPain-Associated Inflammation[J].JournalofFood andDrugAnalysis.2005,13(3):225-231.

[0007] [2]López-Iglesias C,Barros J,Ardao I,Monteiro FJ,Alvarez-Lorenzo C,Gómez-AmozaJL,García-GonzálezCA.Vancomycin-loadedchitosan aerogelparticlesforchronicwo-undapplications[J].Carbohydr Polym.2019,15(204):223-231.

[0008] [3] Saini A, Yadav C, Sethi SK, Xue BL, Xia Y, LiK, Manik G, Li

[0009] [4]DongK, ZhangY, Zhang L, Wang Z, RenJ, QuX. Facilepreparationofmetal-orga-nic frameworks-based hydrophobic anticancerdrug delivery nanoplatform for targetedandenhancedcancer treatment[J].Talanta.2019,194:703-708. Summary of the invention

[0010] The present invention provides a method for constructing an aerogel solid drug delivery system for treating blepharitis. The specific technical scheme is as follows:

[0011] A method for constructing an aerogel solid drug delivery system for treating blepharitis comprises the following steps:

[0012] Step 1, dissolving a polar drug in anhydrous ethanol to obtain solution A, adding the dried and activated metal framework carrier to solution A, stirring, centrifuging, and drying to obtain a polar drug-metal framework drug delivery system; the polar drug is a substance extracted from Ruyi Jinhuang Powder using an alcohol solution with a mass fraction of 30%; the metal framework carrier includes a combination of one or more of CuBTC and IRMOF-3;

[0013] Step 2: After the glacial acetic acid solution of the aerogel material, the polar drug-metal frame drug delivery system and the cross-linking agent are mixed, the mixture is fully cross-linked, and the volatile oil component is added and stirred until there are no bubbles to obtain a mixed glue solution B; or after the glacial acetic acid solution of the aerogel material, the volatile oil component and the cross-linking agent are mixed, the mixture is fully cross-linked, and stirred until there are no bubbles to prepare a volatile oil component-aerogel, the volatile oil component-aerogel is crushed into a thick liquid state, the polar drug-metal frame drug delivery system is added, and the mixture is stirred evenly to obtain a mixed glue solution C; the aerogel material comprises a combination of one or more of chitosan, sodium alginate, silk fibroin, and polyvinyl alcohol; the volatile oil component is the volatile oil extracted from Ruyi Jinhuang Powder by steam distillation or supercritical carbon dioxide; the cross-linking agent is a 2% by mass calcium chloride aqueous solution;

[0014] Step 3: freeze-dry the mixed gel solution B or the mixed gel solution C to obtain an aerogel solid drug delivery system for treating blepharitis.

[0015] Furthermore, in step 1, the mass fraction of the polar drug in solution A is 20%-80%.

[0016] Furthermore, in step 1, the mass ratio of the polar drug to the metal framework carrier is 1:2.

[0017] Furthermore, in step 2, the mass ratio of the aerogel material, the polar drug-metal frame drug delivery system, the cross-linking agent and the volatile oil component is 15:40:5:40.

[0018] Furthermore, in step 2, the mass fraction of the glacial acetic acid solution is 60%, and the mass fraction of the aerogel material in the glacial acetic acid solution of the aerogel material is 3%.

[0019] Furthermore, in step 2, the temperature at which the cross-linking reaction occurs is controlled at -20°C to 40°C.

[0020] Furthermore, in step 1, the stirring time is 1-8 hours, the drying temperature is 80° C., and the drying time is 12 hours.

[0021] Furthermore, in step three, the mixed gel solution B or the mixed gel solution C is dispersed on a multi-well plate, 0.2-0.8 mL is added to each well, and then freeze-dried.

[0022] Compared with the prior art, the present invention has the following beneficial effects:

[0023] The present invention uses the organic metal framework as a carrier and also as an antibacterial absorption dressing, releasing metal ions to kill bacteria when absorbing exudate. There are many similar effects of heavy metals in ancient Chinese medical books. For example, the "Kaibao Materia Medica" mentions that the main treatment of copper is "to treat fractures, disperse blood and stop pain, and break up accumulation." Modern research shows that its mechanism of action is mainly based on the denaturation of heavy metal ions on cell proteins, so that less drug-resistant bacteria are produced, and the present invention needs some new antibiotic-free antibacterial drugs to treat bacterial infections. In the present invention, the organic metal framework is wrapped in the aerogel pore structure, so that the metal ions are gradually released, which can avoid excessive deposition of metal ions, and its bactericidal activity is significantly improved, and the bactericidal effect is significantly higher than that of traditional dressings. It can be made into an eye patch to play an antibacterial and synergistic role. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 This is a scanning electron microscope image of the aerogel solid drug delivery system for treating blepharitis constructed by the doping method of the present invention;

[0025] Figure 2 It is the adsorption-desorption isotherm of the aerogel solid drug delivery system for the treatment of blepharitis constructed by the doping method of the present invention, wherein ADS is the adsorption curve; DES is the desorption curve, Va refers to the adsorption amount of N2, STP refers to the standard state: 273.15K, 100kPa, P / P0 is the relative pressure, P0 represents the saturated vapor pressure of the gas at the adsorption temperature, and P represents the pressure of the gas phase at the adsorption equilibrium. DETAILED DESCRIPTION

[0026] The technical solution of the present invention will be clearly and completely described below in conjunction with the drawings and embodiments. Obviously, the described embodiments are only part of the embodiments of the invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0027] Example 1

[0028] In situ synthesis method to construct aerogel drug delivery system for the treatment of blepharitis

[0029] Take 500g of the medicinal materials in the prescription of Ruyi Jinhuang Powder, steam distill to obtain the volatile oil component, add 3500ml of 30% ethanol solution to the residue after distillation, reflux extract 3 times, each time for 1h, collect the extract and concentrate it to a density of 1.5g / cm 3 The thick paste is a polar drug.

[0030] 100 mg of polar drug was accurately weighed and completely dissolved in 200 ml of anhydrous ethanol at 25°C to obtain solution A. 200 mg of dried and activated CuBTC nanocarrier was accurately weighed and added to the above solution A, magnetically stirred for 6 hours for drug loading, centrifuged at 10,000 rpm for 5 minutes, excess ethanol solution of polar drug was removed, and the precipitate after centrifugation was collected and dried in a vacuum drying oven at 80°C for 12 hours to obtain drug-loaded nanoparticles, i.e., polar drug-metal frame drug delivery system.

[0031] A 3% mass fraction of aerogel material (chitosan) in glacial acetic acid solution (the mass fraction of the glacial acetic acid solution is 60%), a polar drug-metal frame drug delivery system and a cross-linking agent (a 2% mass fraction of calcium chloride aqueous solution) were mixed and placed in an environment of 25°C for full cross-linking; volatile oil components were added and stirred until there were no bubbles; the cross-linked mixed glue was poured into a 24-well plate (the bottom diameter of a single well was 15.6 mm, the area was 1.9 cm 2 ), add 0.6mL of liquid to each well and cool. Place the 24-well plate in a -20℃ refrigerator for pre-freezing for 24h; place it in a vacuum freeze dryer, freeze-dry it for 12h at -20℃ and 1.0mBar, and take it out to obtain the metal frame / aerogel drug delivery system, i.e., the aerogel solid drug delivery system for the treatment of blepharitis (Sample I); wherein the mass ratio of the aerogel material, the polar drug-metal frame drug delivery system, the cross-linking agent and the volatile oil component is 15:40:5:40.

[0032] Example 2

[0033] Construction of aerogel drug delivery system for the treatment of blepharitis by doping method

[0034] A 3% mass fraction of aerogel material (chitosan) in a glacial acetic acid solution (the mass fraction of the glacial acetic acid solution is 60%), a volatile oil component and a cross-linking agent (2% calcium chloride aqueous solution) are mixed evenly, placed in an environment of 25°C for sufficient cross-linking, and stirred until there are no bubbles to prepare a volatile oil component-aerogel; a homogenizer is used to break it into a thick liquid state, and the polar drug-metal frame drug delivery system prepared by the method in Example 1 is added, stirred until the mixture is uniform, and freeze-dried to obtain a metal frame / aerogel drug delivery system, that is, an aerogel solid drug delivery system for the treatment of blepharitis (sample II); wherein the mass ratio of the aerogel material, the polar drug-metal frame drug delivery system, the cross-linking agent and the volatile oil component is 15:40:5:40.

[0035] Evaluation index system

[0036] Ⅰ Exploring the drug release rules by quantitative fingerprint

[0037] The multi-index quantitative fingerprint method was used to determine the content of each index by GC and LC. The in vitro release was determined by the Franz diffusion cell test. Samples were taken every hour within 12 hours, and the fingerprints at different times were measured respectively. The in vitro cumulative release was determined using β-eucalyptol, zingerbium flavonoids, licorice glycoside, rhein, berberine, genistein and glycyrrhizin G2 in the sample as indicators. The original total content of each component in the original extract was regarded as the amount released 100%, and the release amount at different times was calculated using the ratio of the corresponding peak area. The cumulative release formula is shown in Formula I:

[0038]

[0039] t is time (h); Q t is the cumulative release at time point t (%); C t is the concentration at time t (measured in peak area); V0 is the total volume of the dissolution medium (900 mL); C i is the concentration at time point i (measured in peak area); V i is the sampling volume at time point i; M is the content of each component (measured in peak area).

[0040] Table 1 Release data of sample I obtained by in-situ synthesis method described in Example 1

[0041]

[0042] Table 2 Release data of sample II obtained by doping method described in Example 2

[0043]

[0044]

[0045] From the comparison of the drug release data in Table 1 and Table 2, it can be seen that the aerogel drug delivery system for the treatment of blepharitis constructed by the doping method releases the drug more completely, so the doping method is selected as the preferred synthesis method.

[0046] Ⅱ Determination of physical properties

[0047] Microscopic morphology characterization: A field emission scanning electron microscope was used to observe the microstructure of sample II obtained by the doping method described in Example 2. The object to be tested was cut with a scalpel and carefully cut into samples of 5 mm × 5 mm and 2.5 mm thick. The cross section was placed upward on a copper table with conductive glue attached and fixed, and then the sample was gold-sprayed by sputtering. Finally, the microscopic morphology of the cross section of the sample was observed by scanning electron microscopy, as shown in FIG. Figure 1 shown.

[0048] Calculation of specific surface area: Sample II was vacuum degassed at 120 °C for 3 h, and the N2 adsorption-desorption isotherm was measured using a specific surface area analyzer (BET). Figure 2 As shown in Figure 3, the isotherm curve shows a closed loop structure, proving that there is a microporous structure in the carrier. The results of the surface area measurement instrument test of sample I and sample II are shown in Table 3. The results show that the surface area, pore volume and pore size of the carrier prepared by the doping method are all higher.

[0049] Table 3 Micropore structure determination of sample Ⅰ and sample Ⅱ

[0050] Sample name <![CDATA[Specific surface area / (m 2 ·g -1 )]]> <![CDATA[Pore volume / (cm 3 ·g -1 )]]> Pore ​​diameter / (nm) Preparation of sample Ⅰ by in situ synthesis 0.252 0.001 16.285 Samples prepared by doping method Ⅱ 1.593 0.010 25.252

[0051] Calculation of carrier loading capacity: Using a thermogravimetric analyzer (TG), 3 to 8 mg of sample was taken and placed in an alumina crucible. In a nitrogen atmosphere with a flow rate of 30 mL / min, the heating rate was 20 ° C / min, and the temperature range was 30 ° C to 800 ° C. The ash content of four samples, aerogel, metal frame, sample I and sample II, was measured. The loading capacity of the carrier was calculated using the following formula VI. The results are shown in Table 4. The carrier prepared by the doping method also has a higher drug loading capacity and is more suitable for drug loading.

[0052]

[0053] Table 4: Calculation of loading rate of samples I and II

[0054]

[0055] Ⅲ Three-dose method to calculate in vitro antibacterial potency, cell-mediated immunity method to evaluate in vitro anti-inflammatory activity

[0056] (1) Calculation of in vitro antibacterial potency

[0057] Weigh appropriate amounts of Ruyi Jinhuangsan, metal frame and sample II, respectively, and dilute them with pH 7.8 phosphate buffer to form standard solution, metal frame solution and test solution. Take 3 generations of Staphylococcus aureus and Escherichia coli culture, and prepare bacterial suspensions with turbidity of 0.5 McFarland turbidity. Take two flat-bottomed double dishes, inject 20mL of culture medium melted after heating and sterilization, take another sterilized culture medium, heat and melt, cool to 48-50℃, divide into two portions, add 1% of the above two bacterial suspensions, shake well, and inject them into two flat-bottomed double dishes respectively, add 5mL to each dish, spread evenly, cool, and put 8 Oxford cups in each dish for standby. Using the three-dose method, take the standard solution, metal frame solution and three different dose groups of test solution of high, medium and low, and add them to the above Oxford cups respectively. Each bacterial suspension corresponds to five samples, three in parallel, and culture at 37℃ for 18h, measure the diameter of the inhibition zone, and use the biological test statistical method to test the samples and calculate the potency. The mass fraction of the test solution in the high-dose group was 80%, the mass fraction of the test solution in the medium-dose group was 50%, the mass fraction of the test solution in the low-dose group was 20%, the concentration of Ruyi Jinhuang San solution was 50 mg / L; the concentration of the metal frame solution was 50 mg / L.

[0058] Table 5: Effects of five samples on the diameter of the inhibition zone of two bacteria ( n=3)

[0059]

[0060] Table 5 shows that the diameter of the antibacterial zone in the high-dose group is significantly higher than that in the Ruyi Jinhuang San group, and the diameter of the antibacterial zone in the medium-dose group is equivalent to that in the Ruyi Jinhuang San group, and the metal frame also has a certain antibacterial effect. The antibacterial effect of the high-concentration drug delivery system on Staphylococcus aureus and Escherichia coli is significantly higher than that in the Ruyi Jinhuang San group, proving that the antibacterial effect is better.

[0061] (2) Evaluation of anti-inflammatory activity in vitro

[0062] RAW264.7 cells were revived and passaged, and high-glucose DMEM medium was added to adjust the cell density and seeded in 96-well plates. The blank group only added high-glucose DMEM medium, and the control group, model group and experimental group added medium containing 10μg / mL LPS to establish a cell inflammation model. The incubator was cultured for 4 hours and discarded. The blank group and the control group added high-glucose DMEM medium, and the experimental group added sample II solution with a mass fraction of 10% prepared by high-glucose DMEM medium and cultured for 24 hours. ELISA kits were used to detect the inhibitory effect of each group of solutions on inflammatory factors.

[0063] The test results in Table 6 show that the VEGF and IL-6 in the model group are higher than those in the blank group, proving that the model was successfully constructed. The VEGF and IL-6 concentrations in both the experimental and control groups showed a downward trend, and the experimental group was better than the control group. This shows that this drug delivery system has a good therapeutic effect on inflammation.

[0064] Table 6 Effects of sample II on VEGF (vascular endothelial growth factor) and IL-6 (interleukin-6) in the inflammatory model ( n=3)

[0065]

[0066] Note: n=3, There were significant differences between each group and the blank group, *P<0.05.

[0067] IV. Digital image quantification technology and enzyme-linked immunosorbent assay for determination of pharmacodynamic indicators

[0068] SD rats were randomly divided into a model group, a positive control group, and an experimental group. The model group was a blepharitis group given normal saline, the positive control group was given the ethanol extract of Ruyi Jinhuangsan (a polar drug) after modeling, and the experimental group was given sample II after modeling. There were 12 rats in each group, and the dressing was changed once a day, and the wound was observed to be completely healed. The digital image of the wound was collected every other day using a digital camera with a 2cm macro, and the image was processed and analyzed using ImageJ. The processing process includes calibration, binarization, background removal, threshold setting, data analysis, and the final healing time is recorded and the wound healing rate is calculated.

[0069] Wound healing rate (%) = (initial area - current measured area) / initial area × 100%

[0070] The data obtained are used SPSS statistical software was used for data analysis, and one-way analysis of variance was used for comparison among groups.

[0071] On the 14th day after intervention, the rats were anesthetized and euthanized by cervical dislocation. 1 g of tissue was cut from the wound of each rat, collected and homogenized, and then transferred to 10 mL centrifuge tubes, and 3 mL of RIPA buffer was added on ice. After incubation on ice for 2 h, centrifuged at 4 ° C and 10000 rpm for 10 min, the supernatant was transferred to a new centrifuge tube, and stored at -20 ° C for subsequent experiments. The contents of interleukin-6 (IL-6), vascular endothelial growth factor kit (VEGF), epidermal growth factor (EGF), and mitogen-activated protein kinase 8 (MAPK8) were determined. After the ELISA reaction was completed, the absorbance was read under a microplate reader, and the content of each detection index was calculated. The wound and surrounding skin tissues were obtained and fixed and preserved. After hematoxylin-eosin staining, the tissue and cell ultrastructure were observed under electron microscope and transmission electron microscope to evaluate the effect of sample II on the healing of blepharitis wounds.

[0072] Table 7 Comparison of wound closure area in rats

[0073]

[0074] Note: n=6, There were significant differences between each group and the blank group, *P<0.05.

[0075] The results are shown in Table 7. There was no obvious infection on the wounds of the rats in each group after surgery. After 14 days, the wounds of the positive control group were basically healed. The wound healing effect of the model group was significantly slow, and the difference was statistically significant (P < 0.05). The wounds of the experimental group have improved significantly. As shown in Table 8, the rat growth factor determination experiment shows that this drug delivery system can significantly reduce the four inflammatory indicators, and its effect is better than that of the control group.

[0076] Table 8 Effects of metal frame / aerogel drug delivery system on growth factors in rat model ( n=3)

[0077]

[0078] Note: n=3, There were significant differences between each group and the negative control group, *P<0.05.

[0079] Ⅴ Toxicity and irritation evaluation

[0080] Cell proliferation test (CCK method) to evaluate cytotoxicity

[0081] Sterilize sample II under ultraviolet light for 24 hours. Place the sterilized sample in 10mL of DMEM medium containing 10% serum prepared in advance as the extraction medium, and centrifuge at 1000rpm after extraction. Add 3T3 cells in the logarithmic growth phase to the extract. At the same time, the high, medium, and low experimental groups, the blank group (without cells) and the control group (100μL cell suspension) were added with DMEM medium containing 10% fetal bovine serum, and placed in a constant temperature incubator at 37°C and 5% CO2 for 24h, 48h, and 72h, respectively. Use an enzyme marker to detect the OD value (absorbance value) at 450nm, and calculate the relative cell proliferation rate P according to the formula:

[0082] P=(OD 实验组 -OD 空白组 ) / (OD 对照组 -OD 空白组 )×100%

[0083] Table 9 Relative proliferation rate of samples II at different concentrations (%)

[0084]

[0085]

[0086] The results in Table 9 show that neither high nor low concentrations of sample II have any effect on the relative cell proliferation rate.

[0087] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.

Claims

1. A method for constructing an aerogel drug delivery system for treating blepharitis, characterized in that: The following steps are involved: Step 1, dissolving a polar drug in anhydrous ethanol to obtain solution A, adding the dried and activated metal frame carrier to solution A, stirring, centrifuging, and drying to obtain a polar drug-metal frame drug delivery system; the polar drug is a substance extracted from Ruyi Jinhuang Powder using an alcohol solution with a mass fraction of 30%; the metal frame carrier includes a combination of one or more of CuBTC and IRMOF-3; the mass fraction of the polar drug in the solution A is 20%-80%, and the mass ratio of the polar drug to the metal frame carrier is 1:2; Step 2: After the glacial acetic acid solution of the aerogel material, the polar drug-metal frame drug delivery system and the cross-linking agent are mixed, the mixture is fully cross-linked, and the volatile oil component is added and stirred until there are no bubbles to obtain a mixed glue solution B; or after the glacial acetic acid solution of the aerogel material, the volatile oil component and the cross-linking agent are mixed, the mixture is fully cross-linked, and the mixture is stirred until there are no bubbles to prepare a volatile oil component-aerogel, the volatile oil component-aerogel is crushed into a thick liquid state, the polar drug-metal frame drug delivery system is added, and the mixture is stirred evenly to obtain a mixed glue solution C; the aerogel material comprises a combination of one or more of chitosan, sodium alginate, silk fibroin, and polyvinyl alcohol; the volatile oil component is a volatile oil extracted from Ruyi Jinhuang San by steam distillation or supercritical carbon dioxide; the cross-linking agent is a calcium chloride aqueous solution with a mass fraction of 2%; the mass ratio of the aerogel material, the polar drug-metal frame drug delivery system, the cross-linking agent and the volatile oil component is 15:40:5:40; Step 3: freeze-dry the mixed gel solution B or the mixed gel solution C to obtain an aerogel solid drug delivery system for treating blepharitis.

2. The method for constructing an aerogel solid drug delivery system for treating blepharitis according to claim 1, characterized in that: In step 2, the mass fraction of the glacial acetic acid solution is 60%, and the mass fraction of the aerogel material in the glacial acetic acid solution of the aerogel material is 3%.

3. The method for constructing an aerogel solid drug delivery system for treating blepharitis according to claim 1, characterized in that: In step 2, the temperature at which the cross-linking reaction occurs is controlled at -20°C to 40°C.

4. The method for constructing an aerogel solid drug delivery system for treating blepharitis according to claim 1, characterized in that: In step 1, the stirring time is 1-8 hours, the drying temperature is 80° C., and the drying time is 12 hours.

5. The method for constructing an aerogel solid drug delivery system for treating blepharitis according to claim 1, characterized in that: In step 3, the mixed glue solution B or the mixed glue solution C is dispersed on a multi-well plate, 0.2-0.8 mL is added to each well, and then freeze-dried.

Citation Information

Patent Citations

  • Plant-based cosmetic mud for deep cleaning skin and preparation method

    CN110074987A

  • Preparation method of metal framework and application of metal framework in targeted activation of endoplasmic reticulum stress

    CN117085146A

  • Preparation method and application of composite aerogel of post-modified aminated ZIF-8 and cellulose

    CN117160431A

  • Chitosan aerogel / MOF-derived ZnO / C porous dielectric wave-absorbing material as well as preparation method and application thereof

    CN118146761A

  • odor reducing personal care products

    DE102016220085A1